A transdisciplinary team approach to scoping reviews: Mapping the polypharmacy literature. Issue 1 (24th October 2017) - Staley, Jennifer; Waldron, Jennifer; Golchin, Negar; Horace, Alexis; Johnson, Hannah; Bolen, Shari; Dawson, Neal; Kleinman, Lawrence; Bakaki, Paul M.
ABSTRACT: Pediatric polypharmacy, the practice of administering or taking multiple medications among children, is known to be a source of both benefits and harms. Yet, despite the importance of understanding its effects, research to date has been inconsistent in the way polypharmacy in children is defined and measured. This makes measuring prevalence and outcomes across different patient groups and clinical specialties challenging. This poster will introduce the work of a transdisciplinary scoping review team that is mapping the relevant literature to produce a standardized definition of pediatric polypharmacy. The findings, which will be informed by applied library and information science (LIS), will benefit research and clinical practice in pharmacy, medicine, pediatrics, neurology and other fields.